2009
DOI: 10.5551/jat.e599
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin Secretion in Four Tangier Disease Patients with ABCA1 Mutations

Abstract: Aim: Tangier disease (TD), caused by deficiency of ATP-binding cassette transporter A1, is characterized by the absence of high density lipoprotein and the accumulation of cholesteryl esters in many tissues. Recently, it has been reported that ABCA1 is expressed in pancreatic cells and mice with specific inactivation of ABCA1 in cells showed markedly impaired insulin secretion, suggesting that ABCA1 deficiency may be involved in diabetes. The aim of the current study was to confirm these findings by the oral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…In fact, in a Japanese study, four subjects affected by overt Tangier disease underwent OGTT and showed progressively increased plasma glucose concentrations until the diagnosis of T2D. The calculated insulinogenic index, an index of early betacell secretion during OGTT, was significantly lower than in controls [48]. This study suggests that the impairment of ABCA1 function may be directly involved in defective insulin secretion.…”
Section: Dyslipidemia Contributing To Diabetes and Vascular Complicatmentioning
confidence: 78%
See 1 more Smart Citation
“…In fact, in a Japanese study, four subjects affected by overt Tangier disease underwent OGTT and showed progressively increased plasma glucose concentrations until the diagnosis of T2D. The calculated insulinogenic index, an index of early betacell secretion during OGTT, was significantly lower than in controls [48]. This study suggests that the impairment of ABCA1 function may be directly involved in defective insulin secretion.…”
Section: Dyslipidemia Contributing To Diabetes and Vascular Complicatmentioning
confidence: 78%
“…In this regard, the Tangier disease is an excellent model of HDL-C particle deficiency, as it is characterized by a mutation in the ABCA1 protein, which causes an impaired function, and eventually an inability of the peripheral cells to remove the excessive cholesterol. The resulting clinical picture is characterized by an increased occurrence to cardiovascular events in these patients and, surprisingly, reduced insulin secretion and hyperglycemia [47,48]. In fact, in a Japanese study, four subjects affected by overt Tangier disease underwent OGTT and showed progressively increased plasma glucose concentrations until the diagnosis of T2D.…”
Section: Dyslipidemia Contributing To Diabetes and Vascular Complicatmentioning
confidence: 99%
“…HDL also reversed the toxic effects of oxidized LDL on beta cells that are associated with apoptosis and cJNK mediated transcriptional repression of the insulin gene caused cJNK mediated (Abderrahmani et al, 2007). Oral glucose tolerance test in a limited number of patients with Tangier disease (that lack or have dysfunctional ABCA1) showed that they had glucose intolerance as compared to controls (Koseki et al, 2009), thus implicating ABCA1, apoA-I and HDL in glucose metabolism. Cell culture studies using primary pancreatic islets cells and a pancreatic -cell line (Min6), showed that lipid free apoA-I or apoA-II or reconstituted HDL increased insulin secretion up to 5-fold in a Ca 2+ dependant manner (Fryirs et al, 2010).…”
Section: Effects Of Hdl On Diabetes Mellitusmentioning
confidence: 99%
“…In vivo and in vitro studies have provided evidence that HDL may have beneficial effects on glucose metabolism (Koseki et al, 2009;Rutti et al, 2009). Ex vivo studies showed that HDL and delipidated apoA-I or S1P decreased IL-1 and glucose-mediated apoptosis and thus increased the survival of human and murine islets.…”
Section: Effects Of Hdl On Diabetes Mellitusmentioning
confidence: 99%
“…However, the human genetic data mentioned before do not unequivocally support the findings made in the genetic mouse models. On the one hand, decreased glucose-induced insulin secretion has been reported in ABCA1-deficient patients with Tangier disease or heterozygous carriers of ABCA1 mutations (Koseki et al 2009;Vergeer et al 2010). On the other hand, mutations in ABCA1 have not been associated with increased risk of diabetes (Schou et al 2012).…”
Section: Beneficial Effects Of Hdl On Insulin Secretionmentioning
confidence: 99%